Mid-term and long-term clinical assessments of a new 1-piece hydrophobic acrylic IOL with hydroxyethyl methacrylate. Issue 5 (May 2020) - Oshika, Tetsuro; Fujita, Yoshifumi; Inamura, Mikio; Miyata, Kazunori
Abstract : The new hydrophobic acrylic IOL containing hydroxyethyl methacrylate, Clareon, offers highly satisfactory surgical outcomes and is free from glistenings and surface light scattering. Abstract : Purpose: To investigate the clinical outcomes after implantation of a new hydrophobic acrylic intraocular lens (IOL) with hydroxyethyl methacrylate (HEMA) at 1 year and 9 years postoperatively. Setting: Three surgical sites in Japan. Design: Prospective case series and retrospective review. Methods: In 110 eyes of 110 patients who underwent phacoemulsification and implantation of a new hydrophobic acrylic IOL (Clareon CNA0T0), clinical data were collected preoperatively and at 1 day, 1 week, 1 month, 6 months, and 12 months postoperatively. Of these eyes, 20 eyes of 20 patients were examined at 9 years postoperatively, and corrected distance visual acuity (CDVA) and clarity of the IOL were evaluated. Results: All 110 patients (110 eyes) completed every follow-up examination up to 12 months postoperatively. At 12 months, a CDVA of 20/30 and 20/20 was obtained in 110 (100%) and 101 (91.8%) of 110 eyes, respectively. The contrast sensitivity function was better than or similar to the age-matched normal controls, and there was no case of posterior capsule opacification requiring a laser treatment. Glistenings and surface light scattering were not seen in any of these cases. At 9 years postoperatively, a CDVA of 20/40, 20/30, and 20/20 was attained in 20 (100%), 19 (95%), and 14 (70%) of 20 eyes, respectively. One eye (5%) was treated with laser capsulotomy for posterior capsule opacification. There was no case of glistenings and surface light scattering. Conclusions: This mid-term and long-term study indicated that the new hydrophobic acrylic IOL with HEMA was safe and effective with excellent postoperative vision. Glistenings and surface light scattering did not develop with this IOL in contrast to its predecessor.